'Why are we stuck in hospital?' Understanding delayed hospital discharges for people with learning disabilities and/or autistic people in long‐stay hospitals in the UK. (11th August 2022) - Ince, Rebecca; Glasby, Jon; Miller, Robin; Glasby, Anne‐Marie
Abstract: Despite longstanding efforts at de‐institutionalisation, around 2000 people with learning disabilities and/or autistic people in England currently live in hospital settings, amidst reports of protracted stays, limited progress towards living more ordinary lives and scandals of abuse and poor care. Yet, there is relatively little research on why people with learning disabilities and/or autistic people are delayed in hospitals, and what exists has significant limitations. In particular, previous studies have rarely talked directly to people with learning disabilities and/or autistic people, their families and frontline staff about their experiences of living or working in such settings, the barriers to discharge and what would help more people to lead chosen lifestyles. This paper presents the findings of a structured literature review conducted between January and March 2021 on delayed discharges of people with learning disabilities in long‐stay hospital settings. It investigated: the proportion of people with learning disabilities delayed in long‐stay hospital settings, the suggested reasons for these delays and the proposed solutions. The literature reported delays for 11%–80% of inpatients in different settings. The reasons reported are related either to particular characteristics of the person (which we find problematic) or limitations of the system supporting them. However, delays were defined and reported inconsistently, reasons usually lacked depth and detail, and the majority of included studies did not engage directly with the people living in long‐stay settings, their families or frontline staff. Without listening to these voices, genuine solutions will be difficult to find.